OPPO'S GLOBAL EXPANSION STRATEGY THROUGH TECHNOLOGY SUPPLY CHAIN OPTIMIZATION - Dhea Amanda Margareta; Andika Drajat Murdani (PT. Jurnal Center Indonesia Publisher, 2026)
This study analyzes OPPO's global expansion strategy through the optimization of its technology supply chain within the framework of the Global Value Chain (GVC). The smartphone industry has experienced rapid growth in recent decades, with increasingly fierce competition among leading manufacturers. OPPO, a Chinese technology company founded in 2004 and part of BBK Electronics Corporation, has demonstrated significant competitiveness in the global market despite facing challenges in maintaining its market share from 2021 to 2024. This study uses a descriptive qualitative methodology, analyzing primary data from OPPO's official documents and secondary data from industry reports and academic literature. Findings show that OPPO implements production sharing in strategic geographic locations, with design and development centralized in China and manufacturing spread across countries that offer labor or infrastructure advantages. The study shows that OPPO's global expansion follows the Uppsala Model of internationalization, starting with culturally and geographically close markets such as Southeast Asia before expanding to more distant regions. Through technology-based supply chain optimization, digital integration, and the adoption of artificial intelligence (AI)-based coordination systems, OPPO has developed the ability to manage complex global networks while overcoming geopolitical challenges and supply chain disruptions. This research contributes to understanding how technology companies from developing countries leverage the Global Value Chain to enhance international competitiveness, providing insights into the relationship between supply chain strategy and the success of global expansion in the highly competitive smartphone industry.